Source attribution of helicopter noise in pristine environments - Mace, Britton Lee, author; Bell, Paul A., advisor; Loomis, Ross J., advisor (Colorado State University. Libraries, 1999)
Helicopter noise has increased dramatically throughout the remaining natural areas of the United States during the past two decades. Federal legislation has been established (National Parks Overflight Acts, 1987, 1997) in order to establish regulations in areas affected by aircraft overflights. Before regulations can be adopted and enforced, however, management alternatives need to be identified and studied. Unfortunately, a limited amount of research has been completed directly examining noise issues in natural environments. Mace, Bell, and Loomis (1999) simulated conditions in the Grand Canyon in order to study the effects of helicopter noise on aesthetic, affective, and cognitive measures in the laboratory. Results indicated that helicopter noise at both a 40 dB(A) and an 80 dB(A) level had a significant effect on landscape ratings of preference, scenic beauty, annoyance, solitude, tranquility, freedom, and naturalness. Furthermore, affect was significantly more negative following exposure to helicopter noise. There is some evidence that individuals wilt tolerate, or even be pleased with, loud mechanical noise if the noise signals that rescue is on the way or that the noise contains some type of value to the individual (Anderson, Mulligan, Goodman, & Regen, 1983; Kariel, 1990). Attribution theory suggests that the source of the noise may be a major moderator of these effects. Specifically, in the present study it was hypothesized that helicopter noise attributed to tourist operations would have a stronger negative effect on ratings of annoyance, preference, naturalness, scenic beauty, solitude, tranquility, and freedom than noise attributed to a Park Service rescue flight or a Park Service flight for remote trail maintenance. Similarly, noise attributed to helicopter tourist operations was also expected to significantly impact positive and negative affect. Based on previous research showing that intermittent and uncontrollable noise exposure does not habituate (Fields, 1990; Griffiths, 1983; Weinstein, 1982), all noise conditions in this study were expected to yield more unfavorable ratings than a nature sound control group. Two hundred university students (106 women and 94 men) completing a research requirement or earning extra credit in a psychology course served as participants in one of four completely between-subjects conditions. Participants rated 30 natural landscapes on level of annoyance, naturalness, scenic beauty, freedom, solitude, tranquility, and overall preference while being exposed to either nature sounds or helicopter noise. Measures of positive and negative affect were also obtained in a pre-post design. Multivariate analyses of variance found that helicopter noise, regardless of its source, had a significant negative effect on all landscape rating scales. Furthermore, the negative effects produced by the helicopter noise, whatever its source, were consistent in all natural environments (mountain peaks, water, forests, deserts, etc.) depicted in this study. Exposure to helicopter noise, whatever the source, also caused a significant reduction in positive affect. Results were interpreted as providing evidence that the mere presence of helicopter noise triggers important reactions, whether the source of the noise is attributed to a tourist overflight, a Park Service rescue flight, or a Park Service backcountry trail maintenance flight. These findings suggest that natural ambient sounds are important and should be taken into consideration when landscapes are being evaluated or when land management decisions are being made.
Keywords: social psychology; recreation; environmental science